A Study on Aperture Slot Size Effect to Wide Band Open Air Gap RLSA Performance - Imran , Mohd Ibrahim; Tharek, Abdul Rahman (2013)
Radial Line Slot Array Antenna is a slot planar antenna. The slot has been arranged radially to create a concentration of wave into a single point. A slot implemented in RLSA is a rectangular aperture type. Most of the researchers in this field used 1mm slot width with half wavelength on the slot length. From the theory, the wider slot width will allow more current flow thus enhanced the antenna performance. This research is studying the effect of slot width to the Radial Line Slot Array Antenna (RLSA). From the simulation and measurement, it is found that the slot width has improved 1dBi gain, 9dB back lobe ratio and the shape of radiation pattern shape.